Pediatric acute kidney injury: new advances in the last decade - Sidharth K. Sethi; Timothy Bunchman; Ronith Chakraborty; Rupesh Raina (The Korean Society of Nephrology, 2021)
Pediatric acute kidney injury (AKI) is a frequently missed complication. AKI has a significant impact on both short- and long-term outcomes in children. Within the last decade, there have been major landmark developments in this field of critical care pediatric nephrology. The topic was searched by two independent researchers using Google Scholar and PubMed and related studies published in the last 10 years. The terms used for the search were 'pediatric acute kidney injury,' 'pediatric acute renal failure,' 'pediatric dialysis,' 'biomarkers,' 'nephrotoxins,' 'nephrotoxicity in children,' and 'pediatric critical care nephrology.' We found that AKI is common in critically ill neonates and children. Among the various definitions, the Kidney Disease: Improving Global Outcomes (KDIGO) definition is most commonly used. In addition, it is imperative to risk stratify sick children at admission in the hospital to predict AKI and worse outcomes as this aids in early management. There are now major landmark trials that describe the epidemiology, prevention, and management guidelines in this field and health care professionals need to be aware they should diagnose AKI early. Overall, this review highlights the landmark studies in the last decade and shows that early diagnosis and management of AKI in 'at risk' children can improve outcomes.